PETROGENESIS OF EOCENE OCEANIC BASALTS FROM THE WEST PHILIPPINE BASIN AND OLIGOCENE ARC VOLCANICS FROM THE PALAU-KYUSHU RIDGE DRILLED AT 20°N, 135°E (WESTERN PACIFIC OCEAN) - D’Antonio, Massimo; Savov, Ivan; Spadea, Piera; Hickey-Vargas, Rosemary; Lockwood, John (Ofioliti, 2024)
The West Philippine Basin (WPB) is a back-arc basin that opened within the Philippine Sea Plate (PSP) between the current position of the Palau-Kyushu Ridge (PKR) and the margin of East Asia. Spreading occurred at the Central Basin Fault (CBF) mainly from 54 until 30 Ma. The PKR was active since ~48 to 35 Ma constituting a single volcanic arc with the Izu-Bonin-Mariana (IBM) Arc. At ~42 Ma ago spreading rate and direction changed from NE-SW to N-S, stopping at ~30 Ma. A late phase of spreading and volcanism took place between 30 and 26 Ma. ODP Leg 195 Site 1201 is located in the WPB, ~100 km west of the PKR, on 49 Ma crust formed by NE-SW spreading at the CBF. From ~35 to 30 Ma, pelagic sedimentation at Site 1201 was followed by turbidite sedimentation, fed mostly by arc-derived volcanic clasts. The geochemical and isotopic features of Site 1201 basement rocks, which represent Eocene WPB oceanic crust, compared with those of Site 1201 volcanics from the turbidite sequence, representing products of the early Mariana Arc (PKR), provide some insights into the early history of the IBM subduction factory. The WPB basement is made up of aphyric to porphyritic basalts with altered olivine, and preserved plagioclase, clinopyroxene and opaques. The PKR volcanics are porphyritic basalts and andesites with plagioclase, clino- and orthopyroxene, hornblende, alkali feldspar and opaques. Variable textures, and degree of alteration suggesting zeolite facies metamorphic grade, characterize both groups of rocks.The mineralogical and geochemical characteristics of the investigated Site 1201 PKR volcanics highlight their calc-alkaline affinity. This feature is at variance with both other PKR rocks, having mostly boninitic and arc tholeiitic affinity, and WPB basement basalt, having tholeiitic affinity, with some characters transitional to arc-like, as expected for a back-arc basin. New Sr and Nd isotope data, coupled with published Sr, Nd, Pb and Hf isotope data (Savov et al., 2006), highlight the Indian Ocean MORB-like character of Site 1201 basement basalts. This suggests that WPB volcanism tapped an upper mantle domain distinct from that underlying the Pacific Plate. The isotopic features of Site 1201 PKR volcanics are more enriched relative to those of basement basalts reflecting higher amounts of subduction-derived component(s) in the source of arc magmas. Th-Nb relationships and isotope geochemistry of the WPB basement and overlaying arc volcanics suggest addition of subducted sediment mostly as siliceous melts, to the mantle source of the arc volcanics. In that respect, Site 1201 PKR volcanics resemble calc-alkaline volcanics of the currently active Mariana Arc. In addition, the calc-alkaline affinity, unradiogenic neodymium, and inferred Middle Oligocene age of PKR volcanics, suggest they might represent an evolved stage of arc volcanism at Palau-Kyushu Ridge, perhaps shortly before the end of its activity.